In what sense do firms evolve? - Bart Nooteboom (Max Planck Institute of Economics, 2008)
Does evolutionary theory help, for a theory of the firm, or, more widely, a theory of organization? In this paper I argue that it does, to some but also limited extent. Evolutionary theories of economies, and of culture, have acquired considerable following, but have also been subject to considerable criticism. Most criticism has been aimed at inappropriate biological analogies, but recently it has been claimed that a 'universal Darwinism', purged of all such mistaken analogy, is both useful and viable. Why should we try to preserve evolutionary theory, and will such theory stand up to sustained critical analysis? How useful is it for theory of the firm? Evolutionary theory appears to be the most adequate theory around for solving the problem of agency and structure, avoiding both an overly rational, managerial 'strategic choice' view of organizations and a 'contingency' view of organizations as fully determined by their environment. Whether universal Darwinism stands up to critical analysis remains to be seen. Here, the focus is on evolutionary theory of organization and of knowledge. Use is made of a constructivist 'embodied cognition' view of cognition and of elements of a cognitive theory of the firm.
Keywords: 330